HUBUNGAN PERSEPSI PEMBERIAN REWARD TERHADAP KEPUASAN KERJA DAN LOYALITAS KERJA KARYAWAN PADA PEKERJA PENDATANG - Ely Kartikaningdyah; Fatimah Rima Ramadhani (Politeknik Negeri Batam, 2017)
This study examines the extrinsic and intrinsic reward relationship to job satisfaction and loyalty work in manufacturing companies in Batam. The reward system consists of a reward desired and expected reward either extrinsic or intrinsic. Job satisfaction can be met if the reward system fair and equitable to all workers according to their contribution to the company and will reduce labor turnover because of their loyalty to the company's labor and employment. Respondents in this study were 239 labor migrants working in manufacturing companies in Batam that reside in the Flats Muka Kuning, an analytical technique used is the analysis of correlation and independent test samples t-test. The results of the hypothesis: there is a positive and significant relationship between reward extrinsic and reward intrinsically desirable to job satisfaction and loyalty work, there is a relationship reward extrinsic and rewards intrinsic to expect on job satisfaction and loyalty work and not there are reward differences in perception between men and women on job satisfaction.